Monetary Policy Pass-Through, Excess Liquidity and Price Spillover: A Comparative Study of Conventional and Islamic Banks of Pakistan - Muhammad Omer (Bank Indonesia, 2019)
This study investigates the comparative pass-through of policy rate to the retail prices, spillover of prices between Islamic and conventional banking systems, and the impact of excess liquidity on these pass-throughs using data from interbank market of Pakistan. The results suggest that the monetary policy shock affect retail prices of Islamic banks similar to conventional banks, confirming the results of earlier studies. Moreover, there is a strong spillover between the prices of two systems; Islamic banks are following (leading) the conventional banks in pricing the lending (deposit) products. Islamic bank has acquired advantage in the deposit pricing by taping the religious depositors, which also may have promoted financial inclusion thereby contributing to the economic growth and improved income distribution in the society. Our findings suggest that the presence of excess liquidity have no effect on pass-through of policy rate in the Islamic system, which is contrary to the prevalent notion. However, excess liquidity significantly affects the spillovers of prices between the systems. These results support the hypothesis that the Islamic banks are investing in interest-based government securities indirectly via conventional banks. Our findings may help in enhancing the regulatory efficiency of the central banks and the conduct of the monetary policy in the countries where dual banking system exists.